The directions of movement for socialism (mas) in Bolivia: the dialogue between foreign policy and diplomacy - Ceppi, Natalia (2021)
Foreign policy and diplomacy are, within the framework of International Relations studies in general, two categories that enjoy great prominence. In practical terms, they have a close, symbiotic bond and even the idea persists that both mean the same thing. However, from a theoretical-conceptual perspective, foreign policy broadly implies the objectives of the state at the international level, while diplomacy reflects the means to achieve them. Based on this, this paper seeks to identify and reflect on the central axes that crossed the dynamics of Foreign Policy and Diplomacy of Bolivia during the three governments of Evo Morales (2006-2019). Likewise, a brief projection is made on this very particular binomial after the return of MAS to power, following the triumph of Luis Arce and David Choquehuanca on October 18, 2020.